Aplikasi Pendeteksi Dini Kanker Serviks Berbasis Android - Herlinah B; Nursuci Putri Husain (Journal of System and Computer Engineering (JSCE), 2023)
Cervical cancer is the growth of a group of abnormal cells in the cervix (mouth of the womb). The lack of knowledge in diagnosing women against cervical cancer is around 60% - 77%. Lack of diagnostic knowledge about cervical cancer symptoms so that many women do not know the symptoms of cervical cancer and have two possibilities whether it is cervical cancer symptoms or symptoms of other diseases. The purpose of the study was to design an Android-based cervical cancer early detection application to monitor cervical cancer early in helping women diagnose independently. The R&D (Research and Development) research method functions to generate, develop and test the effectiveness of the product (an android-based cervical cancer early detection application) and the forward chaining method functions in making decisions based on the facts that are inputted so as to produce conclusions. home menu, diagnoses, diagnostic results and profiles, starting with the user clicking the diagnosis menu in selecting the symptoms he is experiencing, then the user clicking the diagnostic results menu to see the results of the symptoms that have been diagnosed and have 4 criteria, namely cervical cancer stage 1, cervical cancer stage 2, cervical cancer stage 3 and cervical cancer stage 4. The conclusion of the application where the functional input and output runs well in accordance with the basic concepts that have been made and can be implemented.